Removal of phenol from pharmaceutical wastewater by bioaugmented microbial fuel cells and evaluation of power production performance - ZHU Yongqiang; SHEN Qian; XU Tingting; LIN Xin (Gongye shui chuli)
Using anaerobic sludge as anode chamber substrate and simulated phenol pharmaceutical wastewater as anode chamber substrate, S. oneidensis MR-1 was added to two-chamber microbial fuel cells(MFC) in the forms of free cells and immobilized cells, to construct a two-chamber MFC with free cells(MFC2) and immobilized cells(MFC3) for simultaneous treatment of phenol pharmaceutical wastewater. A two-chamber MFC(MFC1) without electrogenic bacteria was used as control group. The effects of the addition form of S. oneidensis MR-1 on the power generation process of the two-chamber MFC were investigated, and the pollutant removal efficiency and microbial community characteristics were analyzed. The results showed that under three cycles of continuous operation, the electricity generation performance and pollutant removal effect of MFC3 system were the best. The maximum output voltage was 633 mV, the maximum power density was 582.7 mW/m2, the open circuit voltage was 835.9 mV, the internal resistance was 398.8 Ω, the average COD removal rate was 82.5%, the average NH4+-N removal rate was 74.1%, the average phenol removal rate was 82.0%, and the average coulombic efficiency was 26.6%. According to high-throughput sequencing results, the abundance of electrogenic bacteria in anode biofilm increased, and the dominant bacteria in anode biofilm were Proteobacteria, Bacteroidota and Firmicutes. Immobilized cell technology has played a role in bioaugmentation of two-chamber MFC, which provides a certain reference value for energy conversion in sewage wastewater, and promotes the synergy of pollution reduction and carbon reduction.